Pengaruh Teknologi Digital terhadap Partisipasi Perempuan dalam Angkatan Kerja di Provinsi Papua - Suhaib, Aida Muthia; Kartiasih, Fitri (Pusat Pengembangan Kebijakan Ketenagakerjaan Kementerian Ketenagakerjaan Republik Indonesia, 2024)
The high participation rate of female in the labor force in Papua Province in 2015-2022 has not been followed by equity in each district/city. One of the targets in the Sustainable Development Goals (SDGs) is to increase women's empowerment through the use of digital or information and communication technology. The difference in ICT development conditions in Papua Province from 2015-2022 is feared to have an impact on the unequal participation of female in the labor force in each district/city. This study aims to find out the general picture of women's labor force participation and digital technology to determine the influence of digital technology on female labor force participation rate (FLFPR). The analysis approach included panel data regression analysis and descriptive analysis, and the data were secondary data taken from the BPS-Statistics Papua Province online publication. The results of the study show that digital technology (mobile phones usage, internet access, and computers usage), the average length of schooling (RLS) of women, the share of the agricultural sector in the GDP, and the average number of children have a significant effect on increasing FLFPR, while the GDP per capita is not significant. Therefore, it is necessary to improve and equitably distribute access and digital infrastructure as well as the ability to use it, especially for women.